The structure of social stratification in the United States - Beeghley, Leonard (Allyn and Bacon, 1996)
This book describes the class structure in the United States, focusing on the way people's class location influences their opportunities. To do this, Beeghley emphasizes three themes. The first theme is that power influences the distribution of resources in the United States. The second theme is that the social structure influences rates of events, mainly because it determines people's range of choices. The third theme is that social psychological factors influence how individuals act on, and react to, the situations in which they find themselves. One purpose of this book is to help readers to understand social inequality from a new angle of vision. Such an orientation implies that social facts are not always what they seem to be, an insight that is fundamental to sociology. For readers interested in society's class structure in relation to individual action and reaction.